The first report of human meningitis and pyogenic ventriculitis caused by Streptococcus suis: A case report. Issue 8 (August 2018) - Yanase, Tomonobu; Morii, Daiichi; Kamio, Satoshi; Nishimura, Ayako; Fukao, Eri; Inose, Yuri; Honma, Yutaka; Kitahara, Nobuo; Yokozawa, Takayuki; Chang, Bin; Oda, Toshimi
Abstract: Streptococcus suis, a gram-positive facultative anaerobe commonly found in pigs, is an emerging zoonotic pathogen. Herein, we describe a case of a 45-year-old male Japanese meat wholesaler with S. suis meningitis and pyogenic ventriculitis. S. suis was isolated from his blood and cerebrospinal fluid culture, and sequence type (ST) and serotype were confirmed to be ST1 and serotype 2, respectively, by multilocus sequence typing and the Quellung reaction. Magnetic resonance imaging (MRI) revealed right labyrinthitis and pyogenic ventriculitis. The patient was treated with ceftriaxone and ampicillin for 24 days; the treatment was deemed successful based on negative blood cultures on day 4. However, the patient experienced hearing loss and a vestibular nerve disorder. S. suis is a rare pathogen in Japan but can cause severe infection and sequelae. To the best of our knowledge, this is the first report of a human case of pyogenic ventriculitis caused by S. suis . Our findings suggest that S. suis infection should be considered when hearing impairment is present in a patient with bacterial infection and that MRI can help detect ventriculitis, which can necessitate a prolonged treatment duration.